EFEKTIVITAS PENGGUNAAN E-FILING DALAM RANGKA MENINGKATKAN KEPATUHAN PELAPORAN SURAT PEMBERITAHUAN TAHUNAN WAJIB PAJAK ORANG PRIBADI - Endang Winarsih; Asyarif Khalid; Forene Yenjeni (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
In an effort to maximize Taxpayer Compliance, the Directorate General of Taxation always optimizes services so as to increase public awareness of orderliness as taxpayers, one way to do tax reform is to utilize information and communication technology by implementing e-filing systems. This research is a Mix Method research in which research combines two research methods at the same time, qualitative and quantitative. The purpose of this study is to determine the Effectiveness of the Use of E-Filing in the Framework of Improving Compliance Reporting the Obligatory Annual Notification of Individuals. The results of this study indicate that the use of e-filing has been successful in increasing the compliance of individual taxpayers by increasing the annual tax return report of individual taxpayers. Taxpayers find it easy to report their annual tax returns by using e-filing. In addition, taxpayers are aware of their obligations as taxpayers. However, there are some obstacles in implementing e-filing, namely the lack of knowledge of taxpayers and the difficulty of convincing taxpayers to use e-filing effectively and efficiently.